2015
DOI: 10.7589/2013-11-316
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE OFTHEILERIA EQUIANDBABESIA CABALLIAS WELL AS THE IDENTIFICATION OF ASSOCIATED TICKS IN SYMPATRIC GREVY'S ZEBRAS (EQUUS GREVYI) AND DONKEYS (EQUUS AFRICANUS ASINUS) IN NORTHERN KENYA

Abstract: ABSTRACT:The role of equine piroplasmosis as a factor in the population decline of the Grevy's zebra is not known. We determined the prevalence of Babesia caballi and Theileria equi in cograzing Grevy's zebras (Equus grevyi) and donkeys (Equus africanus asinus) in northern Kenya and identified the associated tick vectors. Blood samples were taken from 71 donkeys and 16 Grevy's zebras from March to May 2011. A nested PCR reaction using 18s ribosomal (r)RNA primers on 87 blood spots showed 72% (51/71; 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Previous studies on donkeys have reported a wide range in the value of (sero)prevalence, this particular study was on the higher side of the range reported. Reported T. equi true (sero)prevalence in donkeys range from approximately 2 to 85% (Turnbull et al, 2002;Chahan et al, 2006;Acici et al, 2008;Machado et al, 2012;Garcia-Bocanegra et al, 2013;Gizachew et al, 2013;Salim et al, 2013) and was similar to the work of Hawkins et al (2015) who found a prevalence of 72% (95% CI: 60.4-81.0%) using PCR. Scrutiny of prevalence values from previous studies is, however, limited due to their unique study designs and the effect of external factors such as husbandry (Kouam et al, 2010a;Garcia-Bocanegra et al, 2013).…”
Section: Personal Observation Doo)supporting
confidence: 76%
See 3 more Smart Citations
“…Previous studies on donkeys have reported a wide range in the value of (sero)prevalence, this particular study was on the higher side of the range reported. Reported T. equi true (sero)prevalence in donkeys range from approximately 2 to 85% (Turnbull et al, 2002;Chahan et al, 2006;Acici et al, 2008;Machado et al, 2012;Garcia-Bocanegra et al, 2013;Gizachew et al, 2013;Salim et al, 2013) and was similar to the work of Hawkins et al (2015) who found a prevalence of 72% (95% CI: 60.4-81.0%) using PCR. Scrutiny of prevalence values from previous studies is, however, limited due to their unique study designs and the effect of external factors such as husbandry (Kouam et al, 2010a;Garcia-Bocanegra et al, 2013).…”
Section: Personal Observation Doo)supporting
confidence: 76%
“…The bulk of published literature describes endemicity in horses leaving the epidemiology of piroplasmosis in donkeys poorly understood despite the species' carrier state potential (Chahan et al, 2006;Kumar et al, 2009;Machado et al, 2012;Gizachew et al, 2013, Hawkins et al, 2015. Studies on equine piroplasmosis in Kenyan donkeys have been previously conducted by Vranova et al (2011) andHawkins et al (2015).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Horses at least can remain carriers of B. caballi for up to 4 years after initial infection (Holbrook et al 1973). All three species of zebra have also been identified as carriers (Lampen et al 2009;Hawkins et al 2015), and T. equi is likely to have first evolved as an infection of zebras before affecting other equids ).…”
Section: Equine Piroplasmosismentioning
confidence: 99%